Structural and Morphological Properties of Undoped and Manganese Doped Hematite Nanoparticles Prepared by Ball Milling Method. (October 2020) - Hadianto, Heri; Amiruddin, Erwin; Venera, Rebi Septiawan Putri; Aprilia, Vivi
Abstract: Hematite nanoparticles of undoped and manganese doped were synthesized from natural sand of Logas District Kuansing Regency Riau Province by ball milling method. Structural and morphological properties of these compounds were studied using X-Ray Diffractometer (XRD) and Scanning electron microscope (SEM) respectively. Crystalline structure, lattice parameters, morphologies of the synthesized compounds were studied and the results are discussed. X-ray diffraction (XRD) confirmed the presence of a hematite (α-Fe2 O3 ) phase. Average crystallite size based on flections (1 0 4) for undoped and manganese doped magnetic iron oxide particles are 39.2 nm and 38.2 respectively. The intensity of (1 0 4) reflection is stronger for magnetic iron oxide synthesized for 60 hours than that of 2 step (60+60) hours ball milling. This indicates the product grown along (1 0 4) direction. The average crystallite size decreases when magnetic iron oxide is doped with 10% Mn as confirmed by SEM images.